2021
DOI: 10.1515/mr-2021-0007
|View full text |Cite
|
Sign up to set email alerts
|

Sympatho-adrenergic mechanisms in heart failure: new insights into pathophysiology

Abstract: The sympathetic nervous system is activated in the setting of heart failure (HF) to compensate for hemodynamic instability. However, acute sympathetic surge or sustained high neuronal firing rates activates β-adrenergic receptor (βAR) signaling contributing to myocardial remodeling, dysfunction and electrical instability. Thus, sympatho-βAR activation is regarded as a hallmark of HF and forms pathophysiological basis for β-blocking therapy. Building upon earlier research findings, studies conducted in the rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 237 publications
0
3
0
Order By: Relevance
“…Charney et al (38), and Golden et al (39) found that therapy with anti-depressive drugs decreases plasma and urinary tract levels of norepinephrine and its metabolites. Du (40) revealed that heart failure is associated with the intense activation of the sympathetic nervous system. This factor plays a vital role in the progression of heart failure, and activation of the nervous and hormonal systems can worsen the heart rate and cause vascular spasms and sodium retention.…”
Section: Session 10mentioning
confidence: 99%
“…Charney et al (38), and Golden et al (39) found that therapy with anti-depressive drugs decreases plasma and urinary tract levels of norepinephrine and its metabolites. Du (40) revealed that heart failure is associated with the intense activation of the sympathetic nervous system. This factor plays a vital role in the progression of heart failure, and activation of the nervous and hormonal systems can worsen the heart rate and cause vascular spasms and sodium retention.…”
Section: Session 10mentioning
confidence: 99%
“…The adrenergic signaling in heart failure is traditionally investigated in cardiomyocytes. Dr. Du comprehensively summarizes the recent research on sympatho-adrenergic system in heart failure [ 14 ]. One of the major recent advances for heart failure research is the role of β-adrenergic signaling in immune cells and fibroblasts in addition to cardiomyocytes.…”
Section: Which Cell Is Responsible Under Pathologic Conditionsmentioning
confidence: 99%
“…A hyperactivation of β-adrenoreceptors of rat cardiomyocytes by ISO in high doses leads to left ventricular dysfunction with ballooning and ischemia-reperfusion injury, which is known to involve oxidative stress, proinflammatory responses, calcium overload, mitochondrial malfunction, and, ultimately, cell death [10][11][12]. Nevertheless, the subcellular mechanisms involved in ISO-induced acute ischemic damage beyond adrenergic overstimulation are still poorly understood [13,14]. Although alterations in mitochondrial function have been identified [10,12,15,16], they have not been thoroughly studied, especially in the acute period.…”
Section: Introductionmentioning
confidence: 99%